2024
DOI: 10.1029/2022jb026180
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Tectonic Evolution of the NW Sulu Sea Basin (SE Asia)

Patricia Cadenas,
César R. Ranero

Abstract: We discuss the tectonic structure, seismic stratigraphy and evolution of the NW Sulu Sea using reprocessed 2D reflection profiles. The NW Sulu Sea is located between the Palawan continental shelf and the Cagayan Ridge and represents the northern part of the Sulu Sea, a marginal sea resulting from Paleogene extension and subsequent Neogene contraction due to convergence between the Palawan and the Philippine blocks. The basin consists of six seismo‐stratigraphic units overlying crystalline basement. Syn‐orogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
(202 reference statements)
0
1
0
Order By: Relevance
“…Gravity and magnetic studies suggested that the NW Sulu Sea was mainly floored by a relict Late Creataceous to Eocene oceanic slice (Liu et al, 2014). However, a recent seismic interpretation revealed riftrelated depocenters overlying crystalline basement in the southeastern part of the NW Sulu Sea, and the riftrelated depocenters consists of uncalibrated but tentatively dated Paleogene to Lower Miocene units (Cadenas & Ranero, 2024). The Cagayan Ridge runs approximately parallel to Palawan Island, and extends northward to the islands of Panay, Romblon and Mindoro (Bellon & Rangin, 1991;Marchadier & Rangin, 1990) (Figure 1a).…”
Section: Geology Offshore Palawanmentioning
confidence: 99%
“…Gravity and magnetic studies suggested that the NW Sulu Sea was mainly floored by a relict Late Creataceous to Eocene oceanic slice (Liu et al, 2014). However, a recent seismic interpretation revealed riftrelated depocenters overlying crystalline basement in the southeastern part of the NW Sulu Sea, and the riftrelated depocenters consists of uncalibrated but tentatively dated Paleogene to Lower Miocene units (Cadenas & Ranero, 2024). The Cagayan Ridge runs approximately parallel to Palawan Island, and extends northward to the islands of Panay, Romblon and Mindoro (Bellon & Rangin, 1991;Marchadier & Rangin, 1990) (Figure 1a).…”
Section: Geology Offshore Palawanmentioning
confidence: 99%